(untitled) - ARIEF DWI PISCESSA, RHEZA (Language Horizon: Journal of Language Studies, 2014)
Jackie’s Experiential Learning in Jack Gantos’ Dead End In Norvelt Rheza Arief Dwi Piscesa English Literature Faculty of Languages and Arts State University of Surabaya rheza.arief@gmail.com Hujuala Rika Ayu, SS., MA. English Department Faculty of Languages and Arts State University of Surabaya ayuhujualarika@yahoo.com Abstrak Pembelajaran adalah suatu proses mengakuisisi sebuah pengetahuan. Karakter utama di novel ini, Jackie Gantos, mendapatkan berbagai macam ilmu melalui pengalaman, belajar, atau dengan diajarkan oleh orang lain. Di Dead End in Norvelt, proses pembelajaran yang banyak terjadi didapatkan melalui pengalaman. Jackie Gantos mendapatkan pengetahuan melalui pengalaman, hal ini dapat dianalisa menggunakan Kolb’s experiential learning. Kolb’s experiential learning adalah sebuah metode pembelajaran dengan cara mewariskan pengetahuan secara langsung melalui pengalaman ke dalam diri seseorang tersebut. Tujuan dari thesis ini adalah untuk memperlihatkan proses dari experiential learning di dalam hidup Jackie dan menemukan faktor-faktor yang mempengaruhi Jackie dalam usahanya untuk mengaplikasikan experiential learning dalam kehidupannya di kota Norvelt. Dengan memunculkan proses experiential learning, dapat diketahui bagaimana sebuah pengalaman diwariskan kepada orang lain serta faktor apa yang memunculkan experiential learning. Setelah experiential learning terjadi, Jackie mendapatkan banyak sekali pengetahuan, contohnya cara menggunakan senjata dengan aman, sejarah dari kota Norvelt, idealism dari seorang Eleanor Roosevelt dan lain lain. Proses mendapatkan pengetahuan ini tampak dalam tabel pembelajaran Kolb’s dan faktor-faktor yang mempengaruhi terjadinya proses experiential learning dari Kolb’s adalah social interaction dan self-realization. Kata Kunci: experiential learning, social interaction, self-realization. Abstract Learning is the acquisition of knowledge. The main character, Jackie Gantos, obtained skills through experience, study, or by being taught. In Dead End in Norvelt, most of the process of learning obtained through experience. Jackie Gantos’ gaining knowledge through experience is analyzed by using Kolb’s experiential learning. Kolb’s experiential learning is a method of learning by inheriting the knowledge directly through experience that happened in a person. The objective of this thesis are to reveal the process of experiential learning in Jackie’s life and finding factors that triggers Jackie’s effort of applying experiential learning in his life in Norvelt. By revealing the experiential learning process, it can be found out how an experience is passed on to others and the factors that triggers experiential learning. After the experiential learning happened, Jackie gain knowledge on many things such as gun safety, history of Norvelt, Eleanor Roosevelt idealism and etc. This process of gaining knowledge is depicted through Kolb’s learning table and the factors that trigger Kolb’s experiential learning are social interaction and self-realization. Keywords: experiential learning, social interaction, self-realization. INTRODUCTION Learning is a process of acquiring knowledge through study. This process of learning usually occurs between students and lecturers in a formal educational school. Educational School gives courses and inheriting skillssuch as Physics, History, Chemist, Math and Language from teacher to children. There is also another way to learn something to gain knowledge and increase our understanding about the world. This way of learning is different from the original way of learning such as studying in a school and comprehend the knowledge that our teacher gives. For example, a farmer boy learn how to plough and plant seeds by seeing his father working at the field. After the boy grew up and strong enough, his father ask the boy to help him work at the field. His father showed him how to plough land, watering the field and keeping away birds from destroying the field. This boy gain knowledge through a different method than the original method of studying which is reading books and attending school. The way of the boy learning through experience, from the events of learning through his dad and working to help his dad, is the experiential learning. Experiential learning is a process of gaining knowledge through experience. This knowledge is a result from the combination of grasping and transforming the experience itself. This theory is a well-known model in education. David Kolb in his book, Experiential Learning Theory, presents a cycle of four elements to define the theory. Experiencing problem, observing the critical problem, making a concept of abstract to solve the problem, and actively experimenting to solve the problem. This process leads to a further critical reflection about the experiment and the result of the experiment. This learning theory is a development of various studies regarding to the cognitive development by Jean Piaget and philosophical perspective of pragmatism by John Dewey. Dewey’s philosophical perspective of pragmatism is conveyed in his statement based on Kolb’s: “ If one attempts to formulate the philosophy of education implicit in the practices of the new education, we may, I think, discover certain common principles … To imposition from above is opposed expression and cultivation of individuality; to external discipline is opposed free activity ;to learning from texts and teachers, learning through experience; to acquisition of isolated skills and techniques by drill is opposed acquisition of them as means of attaining ends which make direct vital appeal; to preparation for a more or less remote future is opposed making the most of the opportunities of present life; to static aims and materials is opposed acquaintance with a changing world … I take it that the fundamental unity of the newer philosophy is found in the idea that there is an intimate and necessary relation between the processes of actual experience and education.” (1938, pp.19, 20) Based on the statement by Dewey, Piaget developed this philosophy and researched Dewey’s perspective into a new method to differenciate the actual learning experience as a set of educational method which invoke a knowledge that build through a relation of experience and education. Piaget’s theory describes how intelligence is built through experience. He defines that intelegence is not an innate internal characteristic of the individual but comes alive as a product of the interaction between the person and his or her environment and action is the key point for Piaget. A person who does experiment gathers experience and gains knowledge through the process. In this case, experiential learning studies the process of transforming the experience into a certain knowledge. Just like the saying of Julius Caesar, “Experience is the teacher of all things.” (40s BC, Commentaries on the Civil War, 2. 8), this process of experiential learning can be found mainly in the character of Jack Gantos in Jack Gantos’ “Dead End in Norvelt”.Jackie Gantos, the main character, living his life of summer days in Norvelt and experiencesmany things through his adventure. Summer days are his moments of hunting season with his dad, helping Miss Volker writing obituaries for the local paper, examining dead body in a Morgue which Bunny’s dad work, investigating the whereabout of Mrs. Dubicki. This actions is the sets of events that can be analyzed as a process of experiential learning of Jackie in the novel. Jackie is always curious about many things, that is why he always gets into trouble. He is a good boy, but his action sometimes make his mom got a headache. This because Jackie always gets a nosebleed everytime he gets too excited, which is his mother always worried about. His adventure in Norvelt somewhat he must complices with his nosebleed problem. In his adventure, Jackie experiences many things, he knows how to safely lock the gun to prevent it blasts accidentally by learning it from his hunting experience with his dad. He also learn how to write using a typewriter while helping Mrs. Volker to write her obituaries for the local paper. This process of learning gains him knowledge through experience that happened through his adventure. It is a concrete fact that people do learn from their experience and for nontraditional students such as minorities, the poor, and mature adults – experiential learning has become the method of choice for learning and personal development. (Kolb, 1984: 3) John Byran Gantos, Jr., better known as Jack Gantos (born July 2, 1951) is an American author of children's books renowned for his fictional character Joey Pigza, a boy with attention-deficit hyperactivity disorder (ADHD). Gantos has won several literary awards, including the Newbery Honor, the Printz Honor, and the Sibert Honor from the American Library Association, and he has been a finalist for the National Book Award. His latest book, Dead End in Norvelt (2011) won the 2012 Newbery Medal. Jack Gantos received both his BFA and his MA from Emerson College. While in college, Gantos began working on picture books with an illustrator friend. In 1976, they published their first book,Rotten Ralph. Gantos continued writing children's books and began teaching courses in children's book writing. He was a professor of creative writing and literature (1978–95) and a visiting professor at Brown University (1986), University of New Mexico (1993) and Vermont College (1996). He developed master's degree programs in children's book writing at Emerson College and Vermont College. Jack Gantos writing career began when he work together on picture books in college with his illustrator friend. In 1976, they published their first book, Rotten Ralph. Gantos cares so much about children by publishing dozens of book regarding to picture books for kids. In his last novel Dead End in Norvelt, he creates a master copy of his childhood life into a dazzling novel that easy to understand with a portion of historical value to give an early history lesson to children. The main point of this study is the experiential learning that Jackie Gantos experience in his hometown of Norvelt. His dad is a former WWII soldier, he kept possession of many memorabilia such as Japanesse rifle and other stuff of war. This interacts Jackie to play with his stuff such as Japanesse rifle and pretend to acts like Jackie is in a war that is played on the screenplay over the neighbor. The story of the novel continue about Jackie’s adventure in his town and learning experience on events such as helping writing historical obituary for Miss Volker, and secretly build an airplane in his garage with his dad. Gantos’ novel Dead End in Norvelt focused more on the life of Jackie Gantos that happened in Norvelt at summer of 1962and the social interaction that happened between him and the people in Norvelt. It leads to a great adventure of him, this makes Jackie learns about many topic that he experiences in his life. Jackie lives for a time in Norvelt, a real Pennsylvania town created during the Great Depression and based on the socialist idea of community farming. Jackie's summer of 1962 begins badly: plagued by frequent and explosive nosebleeds, Jackie is assigned to take dictation for the arthritic obituary writer, Miss Volker, and kept alarmingly busy by elderly residents dying in rapid succession. Then the Hells Angels roll in. Gore is a Gantos hallmark but the squeamish are forewarned that Jackie spends much of the book with blood pouring down his face and has a run-in with home cauterization. Gradually, Jackie learns to face death and his fears straight on while absorbing Miss Volker's theories about the importance of knowing history. Based on the explanation above, this study would like to discuss on Kolb’s Experiential Learning Theory by focusing on Jackie Gantos character. And this experiential learning theory will guide us on how to elaborate the process of learning by experience that happens in Jack Gantos’ Dead End in Norvelt by examining Jackie Gantos character and his social interaction with the people of Norvelt. RESEARCH METHOD This study takes the data source of a novel Dead End in Norvelt, written by Jack Gantos which is published in New York by Farrar Straus Giroux, with ISBN: 978-0-374-37993-3 in 2012. To collect the data, the first step is Extensive Reading. Extensive reading is denoted as reading the text of novel extensively in order to collect the data of analysis, such as narrations, monologues, dialogues, quotations, and so forth. After collecting the data by reading extensively, the second step is intensive reading. This step is used in order to reveal the hidden idea of the novel which is related to the data. After finding the hidden idea of the novel, the next step is classifying the data through the novel which needed in analyzing the data, such as speech, actions, characters, behavior, attitudes, and thoughts. The third step is observation the data. This step is the most important step because this step is used in order to find out the experiential learning. In Dead End in Norvelt, The main character Jackie experiences many things that gain him knowledge throughout the novel. Therefore, the experiential learning is very appropriate to be applied to this study. Last but not least, it reaches the final process of collecting data, which is placing the classified data into the table. It is done to simplify in reading the data for the purpose of doing analysis. After finding the experiential learning through the events that correlate Jackie with the major characters based on the novel, the last step is data analysis. This step attempts to answer the questions subsequently based on the statement of the problems by using relevant theory. Besides, this step also uses the data of the novel Dead End in Norvelt which consists of monologues, dialogues, and quotations. The first statement of problem is the occurance of experiential learning. The depiction of experiential learning is using the theory of Kolb. This depiction can be seen on the events that correlate Jackie with other main characters inside the novel. The second statement of problem is the factors that causes Jackie to apply experiential learning in his life which gain him knowledge through experience with other. The factors will be analyzed by using the theory of Rummels. EXPERIENTIAL LEARNING Experiential learning is a well-known model in education. Kolb's experiential learning theory defines experiential learning as "the process whereby knowledge is created through the transformation of experience. Knowledge results from the combination of grasping and transforming experience." (1984:38) Kolb's Experiential Learning Theory (1984:42) presents a cycle of four elements: The cycle begins with an experience that the student has had, followed by an opportunity to reflect on that experience. Then students may conceptualize and draw conclusions about what they experienced and observed, leading to future actions in which the students experiment with different behaviors. This begins the cycle anew as students have new experiences based on their experimentation (Oxendine, Robinson and Willson, 2004). Although this continuum is presented as a cycle, the steps may occur in nearly any order. This learning cycle involves both concrete components (steps 1 and 4) and conceptual components (steps 2 and 3), which require a variety of cognitive and affective behaviors. Experiential learning can exist without a teacher and relates solely to the meaning of making process of the individual's direct experience. However, although the gaining of knowledge is an inherent process that occurs naturally, for a genuine learning experience to occur, there must exist certain elements. According to Kolb, knowledge is continuously gained through both personal and environmental experiences. He states that in order to gain genuine knowledge from an experience, certain abilities are required: • The learner must be willing to be actively involved in the experience; • The learner must be able to reflect on the experience; • The learner must possess and use analytical skills to conceptualize the experience; and • The learner must possess decision making and problem solving skills in order to use the new ideas gained from the experience. Experiential activities are among the most powerful teaching and learning tools available. Experiential learning requires self-initiative, an "intention to learn" and an "active phase of learning”. Kolb’s cycle of experiential learning can be used as a framework for considering the different stages involved. Jennifer A. Moon has elaborated on this cycle to argue that experiential learning is the most effective when it involves: 1) a "reflective learning phase" 2) a phase of learning resulting from the actions inherent to experiential learning, and 3) "a further phase of learning from feedback". This process of learning can result in "changes in judgment, feeling or skills" for the individual and can provide direction for the "making of judgments as a guide to choice and action". Most educators understand the important role of experience in the learning process. The role of emotion and feelings in learning from experience has been recognised as an important part of experiential learning.While those factors may improve the likelihood of experiential learning occurring, it can occur without them. Rather, what is vital in experiential learning is that the individual is encouraged to directly involve themselves in the experience, and then to reflect on their experiences using analytical skills, so they gain a better understanding of the new knowledge and retain the information for a longer time. Reflection is a crucial part of the experiential learning process, and like experiential learning itself, it can be facilitated or independent. Dewey wrote that "successive portions of reflective thought grow out of one another and support one another", creating a scaffold for further learning, and allowing for further experiences and reflection. This reinforces the fact that experiential learning and reflective learning are iterative processes, and the learning builds and develops with further reflection and experience. Facilitation of experiential learning and reflection is challenging, but "a skilled facilitator, asking the right questions and guiding reflective conversation before, during, and after an experience, can help open a gateway to powerful new thinking and learning". Jacobson and Ruddy, building on Kolb's four-stage Experiential Learning Model and Pfeiffer and Jones's five stage Experiential Learning Cycle, took these theoretical frameworks and created a simple, practical questioning model for facilitators to use in promoting critical reflection in experiential learning. Their "5 Questions" model is as follows: • Did you notice...? • Why did that happen? • Does that happen in life? • Why does that happen? • How can you use that? These questions are posed by the facilitator after an experience, and gradually lead the group towards a critical reflection on their experience, and an understanding on how they can apply the learning to their own life. Although the questions are simple, they allow a relatively inexperienced facilitator to apply the theories of Kolb, Pfeiffer, and Jones, and deepen the learning of the group. SOCIAL INTERACTION According to R.J. Rummel (1976: Chapter 9 : Social Behavior And Interaction) , social interactions are the acts, actions, or practices of two or more people mutually oriented towards each other's selves, that is, any behavior that tries to affect or take account of each other's subjective experiences or intentions. This means that the parties to the social interaction must be aware of each other--have each other's self in mind. This does not mean being in sight of or directly behaving towards each other. Friends writing letters are socially interacting, as are enemy generals preparing opposing war plans. Social interaction is not defined by type of physical relation or behavior, or by physical distance. It is a matter of a mutual subjective orientation towards each other. Thus even when no physical behavior is involved, as with two rivals deliberately ignoring each other's professional work, there is social interaction. Moreover, social interaction requires a mutual orientation. The spying of one on another is not social interaction if the other is unaware. Nor do the behaviors of rapist and victim constitute social interaction if the victim is treated as a physical object; nor behavior between guard and prisoner, torturer and tortured, machine gunner and enemy soldier. Indeed, wherever people treat each other as object, things, or animals, or consider each other as reflex machines or only cause-effect phenomena, there is not social interaction such interaction may comprise a system; it may be organized, controlled, or regimented. According to Arnold W Green in his book Sociology an Analysis of life in Modern Society, Social interaction is “…the mutual influences that individuals and groups have upon one another in their attempts to solve problems and in their striving toward goals. Social interaction discloses the concrete results of striving behavior upon roles, statuses, and moral norms” (Green, 1964: 57) There are two types of social interaction, structured and unstructured. Structured social interaction is guided by previously establishing definitions and expectations, owing either to familiarity with the other as a person, as among family and friends, or to knowledge of the others formal position, as between lawyer and judge in court room proceedings, unstructured encounters lack prior expectations and must be defined as required in the course of action. Although at a proposition of intimate relationships are highly structured even the most familiar partners and friends remain capable of unpredictable and novel responses in relationships infact the most interesting trends and associates are those who widely improvise. Conversely rarely do we find a situation completely lacking in structure. Even two strangers come from quite diverse backgrounds, their interactions of likely to be governed by norms of physical safety, age, sex, etc. Thus special interaction may be viewed as partly governed by pre-established rules and expectations and as partly inventive, interpretive and improvisational. TYPES OF SOCIAL INTERACTION According to Chris Levy (earthlink.net: ch.4, 2), Social interaction is divided into five points: a. Exchange: The process in which people transfer goods, services, and other items with each other. Exchange is a social process whereby social behavior is exchanged for some type of reward for equal or greater value. b. Competition: Process by which two or more people/groups attempt to obtain the same goal. Scarce resources are unequally distributed. This concept is very familiar and important to Americans considering the idea of competition is built in to our economy and society. Yet, the jury is still out whether this competition produces the assumed results of the “best rising to the top” c. Cooperation: The process in which people work together to achieved shared goals. Usually this involves the giving up of individual goals for group goals d. Conflict: The process by which people attempt to physically or socially conquer each other. Although war is the most obvious example of this, this is done most often in social situations (ex. politics, threats, etc.) e. Coercion: Process by which people compel other people to do something against their will – based ultimately on force. The state usually handles this through official means (police, army, etc.) but individuals use it in social situations as well (parents, friends, lovers – sex) f. No one type of interaction describes social reality – it involves a mix and match of different ones. SELF-REALIZATION Self-realization is a concept where people realize on their own regarding a certain event that perceived through their behavior. Mortimer Adler defines self-realization as freedom from external coercion, including cultural expectations, political and economic freedom, and the freedom from worldly attachments and desires etc. (1958: 127, 135, 149). This concept is the opposite of social interaction because self-realization occur without any social interaction. The person is free to realize his own potential by absorbing the knowledge through his own way, for example reading books, without any interference from other person. PARADIGM OF ANALYSIS The analysis will utilize Kolb’s experiential learning to classify the events into two triggering factors of experiential learning, social interaction and self-realization. The classification will further explain the process of gaining knowledge. The table of Kolb’s experiential learning is used to reveal the process of learning that a person went through. The process of a person learning through experience consists of Experience phase, Critical Reflection phase, Abstract phase, Active Experimentation phase and reach into a further Critical Reflection to adjust the knowledge that gained through the process. The social interaction and the self-realization is used as a triggering factor of experiential learning process. THE DEPICTION OF JACKIE GANTOS’ EXPERIENTIAL LEARNING Elaborating event in the novel to show the depiction of Jackie’s effort in applying experiential learning is an important process. Before elaborating the event, knowing Jackie’s character first is essential. The knowledge regarding Jackie’s character is important because it is used as a guidance to define the social interaction between Jackie and other character in the event, to understand Jackie relation with others, and to understand the experiential learning process. Jack is a teenager in Norvelt around age of 11 to 12, He is a curious person, a rebel, nose bleeder, a book-worm, helpful to others and also full of action. These characteristics are described throughout the novel as Jack likes to read history when he was at home. His adventures rotates about the stories in Norvelt, how he spent his summer holiday at home grounded because of gun accident and helping Miss Volker out with her obituary thing. Jack is the main character that is full of action through all the novel. Based on Kolb’s experiential learning model, Jackie’s character experience and learn about many things that happens in his life, especially through his social interaction with others as one of the factor to trigger experiential learning. This experiential learning process appears in events that related to Jackie’s action with other character, creating a situation which lead to a learning comprehension through experience. In this section, the events will be distinguished into the most unique event showing Jackie’s learning through experience. This unique event will focus on Jackie’s interaction with some of the most important characters in the novel, Jackie’s parent, Miss Volker, Mr. Spizz, Bunny, and Mrs. Dubicky. THE EVENTS OF JACKIE’S PARENT There are several events that involve Jackie with his parents in the novel. Some of them can be classified as unique, one of them is about the Money and Barter concept. Norvelt is a community town based on barter or trading skills with neighbors. Norvelt is created to solve Great Depression problem. At that time, money is hard to get and crops prices fell so low so business all over town is bankrupt. The concept of Money and Barter shows differences of ages between Jackie’s mom in the past and present time. This event happened between Jackie and his Mom when they visit the doctor to examine Jackie’s nose problem. Jackie learn about the concept of Money and Barter from the conversation with her mom which happened while Jackie is on his way home. The concept of Money and Barter is one of the unique values of knowledge that Jackie experiences in the novel. The other unique event Jackie’s experience with his Dad regarding gun safety that he experienced in the past. This event is important since it builds Jackie’s character to be aware and always caution regarding gun safety. To describe the social interaction happened in the event, knowing the character of Jackie’s parent character is compulsory. The character of a person can define the social interaction that occur between him and other people. In a family relation, social interaction that mostly happened is cooperation between family and also conflict which bonds family members. Jackie’s Mom is a caring, loving mother but is also strict about the rules at home. She forbids Jackie to play with dangerous things like guns and stuffs from the Japanese war that Jackie’s dad kept at basement. “Well, don’t hurt yourself,” Mom warned. “And if there is blood on some of that stuff, don’t touch it. You might catch something, like Japanese polio.” (Gantos, 2012: 1) Her love for Jack is strong even though Jack does things that make her mad like blasting the rifle or mowing the corn row. She always reminds him to be careful because of his nosebleed problem. She’s afraid that her son has iron-poor blood he may not be getting enough oxygen to his brain. (Gantos, 2012: 3) Meanwhile Jackie’s dad is a former war soldier, a hardworking father, and a loving and adventurous man. He learns almost everything from his dad. No wonder Jack is so hyperactive. Jackie’s Dad is also a collector. He keeps stuff from the Japanese War era to make profit when it is valuable enough. This can be seen in the quotation below. … in fact, he never let me play with it, because as he put it, “This swag will be worth a bundle of money someday, so keep your grubby hands off it.”(Gantos, 2012: 1) As the story goes, Jackie will get involved in something more than just a rifle to be blasted. MISS VOLKER’S EVENTS Miss Volker is a medical examiner of the town and also the chief nurse in town. Her job is to take notes of the people health records and writes people obituary as they are passed away. Unfortunately her hands are not as good as her youth. So she asks Jackie’s mom to send Jack to help her with her writing. The job was a tribute of duty from Eleanor Roosevelt and also her way to thank Mrs. Roosevelt for building Norvelt into a friendly community town. “When Mrs. Roosevelt hired me to be the chief nurse and medical examiner of this town I was given a typewriter so I could keep health records on the original two hundred and fifty families. Now it’s my closing tribute to Mrs. Roosevelt that I write their final health report – which, in this case, would be their obituary…” (Gantos, 2012: 16) Miss Volker important is the main point of the novel and her relation with Jackie as her scribe invoke Jackie’s learning phase in experiential learning. By helping her to write obituary, Jackie finds many things that he doesn’t know before and some of the most important and unique event that binds Jackie with Miss Volker are the Eleanor Roosevelt’s idealism and also the history of Norvelt. Eleanor Roosevelt’s idealism is conveyed through Miss Volker speech when she was dictating Jackie to write the obituary of Mrs. Dubicki. The event gives a unique description regarding Eleanor Roosevelt’s thought and idealism of a strong community based town to start a helping neighborhood so people doesn’t have to depend on money which is hard to get in Depression era. She made sure that the community had real houses which include bedrooms, a living room, a kitchen and a bathroom with bathtub. When the government reacts to this idea, they try to reject the plan by calling it luxury living. But Mrs. Roosevelt defended the plan by saying that this is not living in luxury but it is called living with dignity. (Gantos, 2012: 88) The other event is learning about the history of Norvelt. The basic role of society is by knowing your own neighborhood history. In this novel Jackie learnt about Norvelt history from many different perspectives but most of them came from Miss Volker’s obituary dictation. The most important dictation is the one when Miss Volker does the obituary for Mrs. Bloodgood because it reveals the story of how the Norvelt name truly came and also the story of equality behind the making of Norvelt as one of the role model for every town in the United States of America. MRS. DUBICKI’S EVENTS Mrs. Dubicki is the old woman at the house of C-27. She is a loner and a grumpy person. There was a time when Mr. Spizz hands her ticket for having an old shabby house, she chase him with her husband’s double-barreled shotgun. “This is her house,” she said. “She hasn’t painted it since 1934. I like Mrs. Dubicki because that busybody Spizz gave her a ticket for having a shabby-looking house and she chased him off the property with her dead husband’s double-barreled shotgun.” (Gantos, 2012: 47) After Jackie visited her in a disguise with Miss Volker to check about her, she reveals her polite side and also a loving grandparent since she didn’t want to miss her grandson’s birthday on July third. The appearances of Mrs. Dubicki in this novel is important because she plays an important role in helping Jackie learns about disguising skill, driving skill and also Eleanor Roosevelt’s idealism. Eleanor Roosevelt’s idealism has been described on the above section, it also correlates Jackie with Mrs. Dubicki since he learnt about Eleanor Roosevelt’s idealism on the dictation of Mrs. Dubicki obituary. Eleanor Roosevelt is fond of Jeffersonian principle that later shaped the planning of Norvelt. She also agrees to Jefferson that every American should have a house with fertile property to be used as a farming site so when money was difficult to come by, a man and woman could always grow crops and have enough food to feed their family (Gantos, 2012: 97). Regarding Jackie’s driving skill and his disguising skill, he learnt about all that when he was accompanying Miss Volker on an investigation on Mrs. Dubicki’s missing a church appointment which then create a rumor of Mrs. Dubicki already resting in peace at her home. That’s why Jackie tries to disguise himself to avoid a false information and he can get away without having to worry about trespassing someone else house. MR. SPIZZ’S EVENTS Mr. Spizz’s events are considered important because Mr. Spizz works for the Norvelt Public Good whose objective is to create a law abiding situation for the good of the neighborhood. Mr. Spizz is a man who feel that he is the most important man in the town, he acts like a sheriff regardless his appearance running around in a giant tricycle. He secretly love Miss Volker since 1912, sending her a box of chocolate every week. …. It read, I’m still ready, willing and waiting. Your swain since 1912 with the patience of Job. – Edwin Spizz.” (Gantos, 2012: 9) He usually looks bossy, law abiding man as he is strict about rules like grass tall law and house paint job law of the community. He always sticks to the rules and always reminded people in the neighborhood. Mr. Spizz’s events is considered important since Jackie always met Mr. Spizz in the crime scene of the death of old women. But some of the most important events are Jackie’s deal with Mr. Spizz and the murderer of old women. In Jackie’s deal with Mr. Spizz, Jackie helps Mr. Spizz to buy a tin can of 1080 poison for an exchange of forgetting the gutter weed ticket fine and also ending the runway zoning law problem that Mr. Spizz wrung about with Jackie’s Dad airplane project. The other event is the murderer of old women. This event takes place at the end of the novel when Mr. Spizz confessed to Miss Volker regarding the murderer that he has done in Norvelt. Jackie found out the story after saving Miss Volker from the basement. The social interaction happened in the events that include Mr. Spizz are coercion and conflict. This happened because Jackie always clashes with Mr. Spizz in one way or another. The example is the gutter ticket and Jackie’s Dad runway. BUNNY’S EVENTS Bunny is a close friend of Jackie. She is a small, funny, brave and sometimes freaky girl with an enormous energy among her. … Bunny was a girl the size of one of Santa’s little helpers. She was so short she could run full speed under her dining room table without ducking. She’d take double position at shortstop and second base… Because she grew up in a house full of dead people she wasn’t afraid of anything.” (Gantos, 2012: 27) She is not an ordinary girl, regarding the fact that her daily routine was watching her dad prepare the dead. Her dad, Mr. Huffer is the man who prepares dead body before burial. He owned the only funeral parlor in town. The events that correlate Jackie with Bunny is unique. The conversation related to the unique preparation of the dead for funeral give Jackie knowledge. He gain the knowledge that to prepare dead body you must sew the mouth shut so it doesn’t open again. Other example of the event is the Hufferville plan. Jackie found out the plan after meeting up with Bunny to accompany her fire patrol duty. The plan give Jackie the knowledge that Mr. Huffer tried to expand his business to another kind of business, which is a plan to build a new town on the land of Norvelt by buying all the land and moving the old house to another location. The social interaction that mostly happened between Jackie and Bunny are cooperation, coercion and also conflict. These social interaction mostly happened in a close friend relationship and it is natural to have a coercion and conflict in this kind of relationship. THE INFLUENCING FACTORS OF JACKIE’S APPLYING EXPERIENTIAL LEARNING IN HIS LIFE To find out the elements of experiential learning the analysis will be divided into two different factors. The first one is the analysis which use social interaction found in the conversation between Jackie and other characters and the action that happened between Jackie and other characters that create an experience reward to be learned by Jackie. The second one is the analysis which doesn’t involve any social interaction at all. So in this second analysis Jackie gain experience through his own critical thinking which can be called self-realization. This analysis will focus on Jackie’s experience in reading history books and Jackie’s thought. EXPERIENTIAL LEARNING INVOLVES SOCIAL INTERACTION The analysis will be divided into two parts, the conversation part between Jackie and other character in the novel and the other is Jackie’s actual experience throughout the novel. The experience can be classified according to the type of social interaction that has been described in chapter two above. Conversation is the basic social interaction that happened between people in life. Conversation is a form of interactive, spontaneous communication between two or more people who are following rules of etiquette. It is a polite give and take of subjects thought of by people talking with each other for company (Conklin, 1912: 22). Conversation used as a tool to deliver thought of a person to another person. Occasionally, the conversation consist of small talk but it also may consist of something intelligent for example a conversation about history fact, which appears a lot in this novel, and other information on special topic such as war experience. In this part, the conversation will be focused on Jackie’s conversation with other characters in the novel that generalize in some specific topic conveyed through the event. The first event considered an important experience learning is the conversation related to Eleanor Roosevelt and her Idealism. This event give Jackie knowledge on Eleanor Roosevelt’s historical background in building Norvelt and also her Idealism through her point of view. Eleanor Roosevelt’s idealism of living in dignity and living without fear of having no money conveyed in Norvelt town. It is originally her idea to build a community town that release the wrath of economic depression by sustaining life through helping each other out. Jackie learns this through several conversation portrayed inside the novel. Norvelt originally comes through a mind of Eleanor Roosevelt. The mind of having a community based town to increase the standard living of the coal miners. The first conversation about Eleanor Roosevelt appears between Jackie and Mr. Fenton. I had asked Mr. Fenton about it and he said he wanted a hundred bucks because it had historic value. “Eleanor Roosevelt was driven around Norvelt in it,” …. Every time her name was mentioned everything went up in price, which was so backward because she wanted everything to go down in price. (Gantos, 2012: 21) Eleanor Roosevelt wanted to build a strong community within Norvelt, to start a helping neighborhood so people doesn’t have to depend on money like they used to. Since the great depression era, Norvelt becomes a model community to start living in a better standard. This can be seen in the next quotation. “But Godmother Roosevelt came to the rescue. She made sure people had real houses - little New England-style houses – and they had bedrooms and a living room and a useful kitchen and a bathroom with a bathtub, and even a laundry room with washing machine. The government called this luxury living. But Mrs. Roosevelt called it living with dignity.” (Gantos, 2012: 88) Eleanor Roosevelt fought for the people, to make sure they had a deserved place to live in. She especially fond of the principle of Thomas Jefferson the third President of USA that every American should have a house enough to plant their own food in their property. This is to maintain that when money was hard to get, they can still living by growing crops to feed their own family. This is also depicted in the quotation below when Miss Volker is making the obituary for Mrs. Dubicki. “Mrs. Roosevelt was especially fond of a Jeffersonian principle that shaped the planning of Norvelt. Jefferson believed that every American should have a house large enough piece of fertile property so that during hard times, when money was difficult to come by, a man and woman could always grow crops and have enough food to feed their family. Jefferson believed that the farmer was the key to America and that a well-run family farm was a model for a well-run government. Mrs. Roosevelt felt the same. And we in Norvelt keep that belief alive.” (Gantos, 2012: 97) Jackie learns a bit of history of Norvelt and also the principal idea of Eleanor Roosevelt that wants to bring Norvelt family into a role model for every town in the United States. This intelligence came from a conversational subject between Jackie and Mr. Fenton and also Jackie and Miss Volker. The process of experiential learning can be seen on the table below. The event between Jackie and Bunny is the preparation of a dead man. In this event, Jackie learns about how the dead being prepared for the last tribute. This event occurs in a conversation between Jackie and Bunny while they were playing baseball on the field. Bunny was asking about Jackie’s doing obituary for Mrs. Slater for the paper. She think that it was well written. So she gives Jackie a gift, dentures from Mrs. Slater funeral preparation. Jackie was surprised to know that Bunny had Mrs. Slater dentures. He thought that it was buried with Mrs. Slater body. Then Bunny tells him a story about how to prepare a dead body for funeral viewing. “You don’t know anything about preparing dead people for a viewing,” she bragged. “If you’ll notice, the stiffs are always displayed with their mouths closed because my dad has to sew their mouths shut. If they don’t have real teeth you just sew their gums together which is actually easier, so we keep the dentures. Dad saves them because when he gets a boxful he donates them to the retirement home and some of those old people reuse them.” “You really have to sew the mouth shut?” I asked. That stunned me. It seemed so brutal. “With an upholstery needle and twine,” she added, knowing she was making me nervous. “It’s like sewing up a turkey after you stuff it, is how my dad puts it.” (Gantos, 2012: 30) Bunny tells him about how his dad sews the dead’s mouth to prevent them from opening. And she also tells him about how the dentures are being kept. Because if someone doesn’t have teeth it is easier to sew the gum where the teeth belong rather than to keep the dentures inside. The dentures will be donated to the old house to be reused by seniors. Bunny also describes the sewing session was like sewing up turkey for Thanksgiving. Imagining it was already too much for Jackie as his nose starting to bleed. This makes Bunny curious and ask Jackie about what happened to his nose. And then Jackie tell Bunny about how his sickness correlated on all things, fear, excited, startled, imagining scary stuff and etc. I felt my blood surge like a tidal wave toward my face. “Are you always like this?” she asked, and pointed her stubby hand at my nose. “Yes,” I croaked, and wiped away a few drops of blood. “You should see a doctor,” she advised. “It’s nothing,” I said. “I have a very sensitive nose. Anything makes it bleed.” (Gantos, 2012: 30) This event helps Jackie to understand more about how to prepare dead body for a funeral. It also helps him to share his problem about his nose to Bunny. It makes Jackie feels comfortable even though he had nose that bleeds a lot. The event of preparing dead body can be disassembled through the table below: Experience Bunny tells Jackie about how to prepare dead people for funeral viewing Critical Reflection Bunny reflected on the event in past about his dad sewing the dead’s mouth Active Experimentation Bunny tell Jackie that the process of sewing the mouth was just like sewing up turkey Abstract Bunny explain further about how the dentures are being kept if the body doesn’t have teeth Further Critical Reflection Jackie knew about how to prepare dead men. And Bunny knew about Jackie’s sickness and what triggers his nose to bleed. EXPERIENTIAL LEARNING WITHOUT SOCIAL INTERACTION This part of analysis will conveyed events that happens in the novel which involving Jackie as the only person who experience it. It occurs without any social interaction with other character. Self-realization is a concept where people realize on their own regarding a certain event that perceived through their behavior. Mortimer Adler defines self-realization as freedom from external coercion, including cultural expectations, political and economic freedom, and the freedom from worldly attachments and desires etc. (1958: 127, 135, 149). In this novel, the self-realization comes into the mind of Jackie Gantos who realize his action and try to comprehend the effect of his action. The first event that reveal the concept of self-realization is the event of Jackie’s rifle. In this part of the story, Jackie is playing with his dad rifle. The old Japanese rifle is still working well, so even though Jackie knew it was dangerous he still plays with it but he let loose the ammo clip to make sure it was not blasting accidentally. I lifted the rifle again and swung the tip of the barrel straight up into the air. I figured I could gradually lower the barrel at the screen, aim, and pick off one of the Japanese troops. With all my strength I slowly lowered the barrel and held it steady enough to finally get the ball centered inside the V, and when I saw a tiny Japanese soldier leap out of a bush I quickly pulled the trigger and let him have it. BLAM! The rifle fired off and violently kicked out of my grip. It flipped into the air before clattering down across the picnic table and sliding onto the ground. … (Gantos, 2012: 4) Based on the narration above, there are no social interaction that happened. According to R.J. Rummels, social interaction requires a mutual orientation. (Hawaii.edu, pars 8) This mean that there must be two or more person available in the interaction and they must be aware of each other. So the text above only represent experiential learning. It only happened because of Jackie’s action, playing with his Dad’s Japanese rifle. There is no other person involved in and there are on mutual orientation happened. The elaboration of the theory can be seen below on the table. Active Experimentation The rifle’s blasting a bullet through the neighborhood yard Abstract Jackie aiming his rifle and pull the triggers like an actual soldier Experience Jackie playing with rifle Critical Reflection Jackie watching war movie and pretend to be a soldier Further Critical Reflection Jackie confuse and try to comprehend about what happened to the gun, why did it blast off and try to be more safe with gun in the future The table explains about how Kolb's experiential learning theory works in this novel. Experience is the first event that take notice of Jack playing with his Dad Japanese rifle. Critical Reflection tells us about Jackie’s thought about his new toy by watching a war movie and pretend to be a soldier. Abstract is the conceptualization of Jackie’s thought about being an actual soldier by aiming his rifle and pull the triggers as if he is in war. Then the Active Experimentation shows the cause of Jackie’s action for playing with his gun. At last Jackie made another further Critical Reflection by showing his confusion about the matter and try to comprehend about what happened to the gun, why it blasted off and he will try to be more careful with gun in the future. The War concept is the next event that appear as a self-realization of Jackie. War is a devastating event. Jackie’s dad is a former marine in World War II so when Jack was digging the bomb shelter he usually asked about war stuff to his dad. In chapter 9, Jackie asked his Dad about war. “Hey, Dad” I called behind him as he walked toward the tractor. “Which do you think is more deadly? Past history or future history?” He didn’t even slow down to think about it. “Future history.” He yelled back without hesitation. “Each war gets worse because we get better at killing each other.” (Gantos, 2012: 52) Jackie then think about his dad statement and began to comprehend about war in the past such as the quotation below. That sounded so true. At first caveman bashed each other’s heads in with rocks and sticks. By the time of the Crusaders it was long swords and arrows, and at Gettysburg they were blasting each other to bits from cannons filled with lead balls, iron chains, railroad spikes, and door knobs. And atomic bombs made future wars look even more hopeless. (Gantos, 2012: 52) He then think about the result of a nuclear war, the effect on earth and also the animals and human being after the radiation take effect. No humans will survive. All the animals will die. Fish will rot in acidic water. All vegetarian will wilt in the polluted air. There will be nothing left but enormous insects the size of dinosaurs. (Gantos, 2012: 52) Jackie then continue to march on his job to dig a bomb shelter. Knowing that the future might get worse than he thinks and the only hope for survival might be by building cities underground just like his Dad used to say that the army built one to protect the president and all the self-important government people. Jackie self-realization appear in the event after his dad tell him about how future war is more deadly because we get better in killing people. He then began to think about the war, how it effects on human life. Another war concept appear in Miss Volker dictation about Mrs. Vinyl when she entered the history part regarding the Hiroshima incident. “ … Most people think that the atomic bombing of Hiroshima was necessary for ending the war.” She continued. “And there is some truth to that, given that the Japanese were prepared to fight to the last person to protect their country. But what the atomic bombing of Hiroshima should teach everyone is that you don’t win the war by being more moral or ethical or nicer or more democratic than your enemy. And God has nothing to do with winning or losing. … You win a war by being tougher and meaner and more ruthless than your enemy. You beat, burn, and crush them into the ground. This is the historic rule of winning a war. …” (Gantos, 2012: 126) But in this part Jackie learn by listening to Miss Volker speech about the obituary, which is not his own self-realization. So, this analysis regarding the Hiroshima incident will not appear in the experiential learning because the table will only focus on the self-realization part of Jackie’s thought about the war. Actual Experimentation Jackie then think about how the caveman fight, and goes throughout history until the atomic incident Experience Jackie digging a bomb shelter he then asked his dad about the war Critical Reflection His dad then answer without doubt that future history is more deadly Abstract His dad give a clear perspective about how war in the future is more deadly by giving statement that people get better at killing people in the future Further Critical Reflection Agreeing his dad, he continued to dig for bomb shelter in hope for a future save compartment when they enter the future history war. CONCLUSION Based on the recent analysis, the result can be concluded that experiential learning appear through events that Jackie’s going through in his summer holiday in Norvelt. Those event occured between Jackie and other characters in the novel. Jackie’s parents, Miss Volker, Mr Spizz, and Bunny are some of the most important characters that build Jackie’s intellectual mind. Experiential learning occured because of the influencing factors, the social interaction that happened between Jackie and the other characters in the novel and also Jackie’s self-realization. The first conclusion is concerning about how the experiential learning happened. The experiential learning appeared because of the events that depict the learning process between Jackie and other characters in the novel. The experiential learning is represented through the Kolb’s experiential learning table so the process of experiential learning can be seen clearly. The experience table shows the event of social interaction between Jackie and the other characters, or the event of self-realization by Jackie himself. These experience table then proceeds into a critical reflection of the problem and encourages Jackie to think about the event which stimulate an abstract conceptualization of the event. Jackie then actively experimented on the abstract that he created from the previous table, to gain a concrete experience which then enabled him to get knowledge regarding the matter. Jackie then created a further reflection of the experience, and think about the result of the experience. This further critical reflection create a scaffold for further learning, and allow for further experiences and reflection. Critical reflection reinforces the fact that experiential learning and reflective learning a